Wavelet analysis of diffuse ultrasonic waves for damage detection - Kumar S.; Wali A.S.; Tyagi A. (My University, 2025)
Diffuse ultrasonic waves can be used to interrogate a large volume of complex structure with high sensitivity using a small number of sensors, but it is difficult to correlate changes in diffuse ultrasonic signals with the health of the structure being interrogated. This paper provides a wavelet-based comprehensive damage detection strategy for diffuse ultrasonic waves. They are generated by an impulse and tone burst and received by broadband piezoelectric transducers. The potential of the technique is examined, and laboratory examples are presented. It is shown that the wavelet carries information about the material damage. The strategy includes a systematic feature extraction method for the declaration of the structural status as "damaged" or "undamaged". © International Workshop on Structural Health Monitoring. All rights reserved.